A shaped tellurium oxide ceramic slug and a method of shaping the same
Patent Information
- Application Number
- CN202610952311.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-29
- Publication Date
- 2026-10-20
AI Technical Summary
[0006]然而,将湿法成型工艺直接应用于氧化碲陶瓷芯块的制备存在一系列技术障碍
1、本发明针对氧化碲粉末密度高、具有毒性且对水分敏感的特点,首次提出采用全真空密闭结合有机载体浆料的湿法成型方法,采用先形成料浆A、后加入固化剂形成料浆B的分步工艺。双酚A环氧树脂作为粘结剂与临时骨架,其分子链上富含环氧基团在固化剂引发下发生开环交联聚合,将氧化碲粉末颗粒牢固包覆并粘结,而酚醛胺类改性胺固化剂通过分子结构中的胺类活泼氢,与双酚A环氧树脂分子链两端的环氧基团发生逐步加成聚合反应,伯胺基(-NH2)上的两个活泼氢先后与两个环氧基发生加成反应,生成仲胺和叔胺结构;仲胺基(-NH-)上的一个活泼氢与一个环氧基发生加成反应,生成叔胺结构,通过化学交联最终形成具有较高内聚强度的三维网络结构。同时,固化剂分子中的酚羟基通过氢键作用与环氧基团发生反应,加速胺类活泼氢对环氧基的开环加成反应加速固化的效果;而固化剂分子中的刚性酚醛骨架在交联反应后被引入树脂网络,进一步提升固化物热变形温度,使坯体在后续加热过程中能够保持形状稳定,赋予陶瓷生坯更高的生坯强度,为后续工艺提供高质量的陶瓷芯块前驱体。
Smart Images

Figure FT_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nuclear energy technology, specifically relating to a molded tellurium oxide ceramic core and its molding method. Background Technology Iodine-131, as an important radionuclide, has irreplaceable application value in the field of nuclear medicine. Iodine-131 emits both gamma rays and beta rays during decay; gamma rays can be used for imaging, while beta rays can be used for treatment. Because iodine is one of the raw materials for synthesizing thyroid hormones, iodine-131 can be selectively taken up and concentrated by thyroid tissue. The average range of its emitted beta rays in tissue is only 1 mm, with almost all energy released within the thyroid tissue, having minimal impact on surrounding tissues. Therefore, it is particularly suitable for the treatment of hyperthyroidism and the removal of residual thyroid tissue after surgery for differentiated thyroid cancer. In addition, iodine-131 can also be used for thyroid function testing and thyroid imaging. Compared with traditional treatment methods, iodine-131 therapy has advantages such as safety, high cure rate, and low recurrence rate, and has become an indispensable tool in the diagnosis and treatment of thyroid diseases.
[0002] Natural tellurium has several stable isotopes, among which tellurium-130 has a large neutron capture cross section. After neutron irradiation, it undergoes a nuclear reaction to generate tellurium-131, which then decays into iodine-131 via β-decay. Therefore, iodine-131 is usually obtained by neutron irradiation of tellurium-130 targets in a reactor. Preparing high-purity, high-density tellurium targets is a prerequisite for obtaining high yields of iodine-131. Regarding target material selection, elemental tellurium or its compounds can be used as raw materials. Tellurium dioxide in oxide form is the most commonly used target material due to its high melting point, good chemical stability, ease of processing, irradiation stability, and chemical properties. Therefore, the quality of the tellurium oxide ceramic core directly affects the irradiation efficiency and the subsequent separation and purification of iodine-131.
[0003] Currently, the conventional method for preparing tellurium oxide ceramic cores is powder metallurgy. Tellurium oxide powder is dried, sieved, and pressed into shape to obtain a green body with a certain shape and strength. This green body is then sintered at high temperature or through reaction sintering to obtain a dense ceramic core. This method is widely used and technically mature in the fields of cermets and oxide ceramics. However, tellurium oxide has strong biotoxicity. Inhalation or skin contact with tellurium dioxide dust can damage the respiratory system, liver, and kidneys, classifying it as a toxic and hazardous substance. In the conventional pressing process, operators need to pour the dried tellurium oxide powder into a mold, level it, and apply pressure to demold. This series of operations makes it difficult to completely avoid dust and spillage. Furthermore, fine tellurium oxide powder particles easily float in the air, forming aerosols that not only pollute the operating environment but also pose a direct threat to the health of operators. Especially in large-scale production or long-term operation, the risk of aerosol generation and accumulation increases significantly. In addition, spilled powder is difficult to clean up completely, potentially causing cross-contamination and further increasing waste disposal costs.
[0004] To address the aforementioned problems in the prior art, those skilled in the art have attempted to improve traditional compression molding processes, such as operating within a sealed glove box, employing wet granulation to reduce dust, and using low-toxicity binders. However, these improvements do not fundamentally eliminate the problems of powder spillage and aerosol formation. While a sealed glove box can confine the powder within a limited space, cleaning and material transfer within the glove box still cause powder to escape; although wet granulation aggregates the powder into larger particles, these particles can still break down and produce fine powder during subsequent compression; adding binders can reduce dust to some extent, but binders are usually liquids or low-melting-point solids, and their introduction may alter the flowability and compressibility of the powder, requiring additional degreasing processes.
[0005] Another approach is to employ a fully wet molding process, such as slip casting, injection molding, or gel casting. This involves dispersing the powder in a liquid medium to create a slurry or suspension, which is then injected into a mold, thus avoiding the dry powder handling process. These methods are widely used in the ceramics industry and are suitable for toxic, flammable, or dust-generating powder materials. For example, the paper "Molding Process of Porous Alumina Ceramics Based on 3D Printed Molds and Gel Casting," published on September 8, 2021, uses photopolymerization 3D printing technology to create high-precision resin molds, combined with gel casting to form porous alumina ceramics. By optimizing the formulation of low-viscosity, high-solid-content alumina ceramic slurry and controlling the quality of the green body using a vacuum pressurization process, porous alumina ceramics with complex shapes were successfully prepared. The research progress on the preparation of porous ceramics by gel casting was published in Shandong Chemical Industry in 2022. It pointed out that the gel casting method has been widely used in the preparation of porous ceramics because it can produce large-sized ceramic products with near-net size and complex shapes. The green body after molding has the advantages of good overall uniformity, few defects and high strength.
[0006] However, directly applying wet forming processes to the preparation of tellurium oxide ceramic cores presents a series of technical obstacles. First, tellurium oxide has a certain degree of water solubility, causing it to dissolve and precipitate in water-based slurries, leading to slurry instability and affecting the compositional uniformity of the green body. Second, tellurium oxide has a high density, making it prone to settling in slurries, thus making it difficult to obtain slurries with high and uniform solid content. Furthermore, methods such as slip casting involve lengthy demolding and drying processes, resulting in lower green body strength and a higher likelihood of cracking and deformation.
[0007] Therefore, the existing conventional dry pressing process for preparing tellurium oxide ceramic cores has significant shortcomings in terms of occupational safety and environmental protection. There is an urgent need to design a safe and controllable new wet forming process tailored to the characteristics of tellurium oxide materials, which can avoid the handling of dry powder while ensuring that the green body has sufficient density and strength to meet the requirements of subsequent sintering and irradiation. Summary of the Invention
[0008] To address the technical challenges posed by the easy spillage and aerosol formation of solid powder in the existing tellurium oxide ceramic core pressing process, which leads to environmental hazards and personnel safety risks, this invention discloses a method for molding tellurium oxide ceramic cores. This method can replace conventional pressing processes for preparing tellurium oxide ceramic core blanks. Not only does it produce tellurium oxide ceramic core blanks with ideal theoretical density, suitable for irradiation production of iodine-131, but the entire molding process is conducted under vacuum and closed conditions, eliminating powder dust and aerosol generation at the source.
[0009] The technical solution of the present invention is as follows: One of the objectives of this invention is to provide a method for forming tellurium oxide ceramic core blocks. Under vacuum and sealed conditions, dried and degassed tellurium oxide powder is mixed evenly with bisphenol A epoxy resin to form slurry A. Then, a phenolic amine modified amine curing agent is added to slurry A and mixed evenly to form slurry B. Slurry B is injected into a metal container and left to stand. Then, it is heated and dewaxed. After heat preservation, the formed tellurium oxide ceramic core block is obtained. Phenolic amine modified amine curing agents are prepared by Mannich condensation reaction of phenolic compounds, aldehyde compounds and polyamine compounds. The amine value is 400-500 mgKOH / g and the viscosity is 300-1500 mPa·s.
[0010] In this step, drying and degassing not only removes the moisture and air physically adsorbed on the surface of the tellurium oxide powder, but also removes the moisture and other volatile impurities released by the tellurite acid produced during hydrolysis inside the powder when heated. This avoids bubble defects during slurry solidification and also prevents the possibility of redox reactions between gases and resin decomposition products during high-temperature processes, ensuring the accuracy of the ceramic core's composition.
[0011] Furthermore, the mass ratio of the tellurium oxide powder to the bisphenol A epoxy resin is (3-4):1. Furthermore, the bisphenol A epoxy resin is of type E-44 or type E-51. Further, the preparation steps of the phenolic amine modified amine curing agent are as follows: phenolic compounds, aldehyde compounds and polyamine compounds are added to a reaction vessel at a mass ratio of 300-500:500-800:100, and stirred and reacted at 80-120℃ for 2-4 hours. After vacuum dehydration, the phenolic amine modified amine curing agent is obtained. The phenolic compound is any one or a combination of phenol, nonylphenol, cashew phenol, and m-cresol; the aldehyde compound is formaldehyde solution or paraformaldehyde; the polyamine compound is any one or a combination of diethylenetriamine, triethylenetetramine, and hexamethylenediamine.
[0012] After this modification method, the product molecules of the phenolic amine modified amine curing agent are introduced with phenolic hydroxyl groups that accelerate autocatalytic curing and rigid phenolic skeletons that improve the heat resistance of the cured product, while retaining the active hydrogen of the amine as active sites for crosslinking reaction.
[0013] Furthermore, the specific steps are as follows: (1) Weigh each raw material according to the mass ratio of phenolic compounds, aldehyde compounds and polyamine compounds in the ratio of 300-500:500-800:100. First add the phenolic compounds at 35-45℃, then add the polyamine compounds in sequence, and stir evenly.
[0014] (2) Under stirring conditions, aldehyde compounds are added in batches as the temperature is gradually increased to 70-80℃. After the addition is complete, the reaction continues at 70-80℃ for a total reaction time of 2-4 h. During the reaction, the lone pair electrons on the amine group undergo nucleophilic addition to the carbonyl carbon in the aldehyde group to generate a hydroxymethylamine intermediate. Subsequently, this intermediate undergoes electrophilic substitution condensation with the ortho or para position of the phenolic hydroxyl group to form a phenolic amine structure containing a phenolic hydroxyl group and an amine group.
[0015] (3) After the reaction is completed, the product is heated under vacuum to remove water and unreacted free phenol and free amine, and a pure phenol-amine modified amine curing agent product is obtained.
[0016] Furthermore, the volume ratio of the slurry A to the phenolic amine modified amine curing agent is (2-3):1. Furthermore, slurry B is injected into a metal container and left to stand for 2-16 hours. Further, slurry B is injected into a metal container and heated to 60-90℃, then left to stand for 2-16 hours. Furthermore, after the metal container containing the injected slurry B is left to stand, it is heated to 550-700℃ for dewaxing, and the holding time is 2-8 hours. The second objective of this invention is to provide a molded tellurium oxide ceramic core.
[0017] Furthermore, the relative density of the molded tellurium oxide ceramic core is greater than 55%.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention addresses the characteristics of tellurium oxide powder, such as high density, toxicity, and sensitivity to moisture. It proposes for the first time a wet molding method using a fully vacuum-sealed organic carrier slurry, employing a stepwise process of first forming slurry A and then adding a curing agent to form slurry B. Bisphenol A epoxy resin acts as a binder and temporary framework. Its molecular chain, rich in epoxy groups, undergoes ring-opening crosslinking polymerization initiated by the curing agent, firmly coating and bonding the tellurium oxide powder particles. The phenolic amine-modified amine curing agent, through the active hydrogen atoms in its molecular structure, undergoes a stepwise addition polymerization reaction with the epoxy groups at both ends of the bisphenol A epoxy resin molecular chain. The two active hydrogen atoms on the primary amine group (-NH2) successively react with two epoxy groups to generate secondary and tertiary amine structures; one active hydrogen atom on the secondary amine group (-NH-) reacts with one epoxy group to generate a tertiary amine structure. Through chemical crosslinking, a three-dimensional network structure with high cohesive strength is ultimately formed. Meanwhile, the phenolic hydroxyl groups in the curing agent molecule react with the epoxy groups through hydrogen bonding, accelerating the ring-opening addition reaction of the active hydrogen of the amine to the epoxy group and thus accelerating the curing effect. The rigid phenolic skeleton in the curing agent molecule is introduced into the resin network after the cross-linking reaction, further increasing the heat distortion temperature of the cured product. This allows the green body to maintain its shape stability during subsequent heating, giving the ceramic green body higher green body strength and providing a high-quality ceramic core precursor for subsequent processes.
[0019] 2. This invention discloses a method for uniformly mixing tellurium oxide powder and bisphenol A epoxy resin to form slurry A. In this slurry, the bisphenol A epoxy resin, in its uncured state, possesses moderate viscosity and good thixotropy. It is water-free, and its hydrophobic molecular structure provides excellent water-repellent properties. This not only promotes thorough wetting of the resin liquid phase on the powder surface, suspending high-density tellurium oxide particles and preventing sedimentation and stratification during slurry preparation and molding, but also effectively avoids the defect of tellurium oxide surface easily adsorbing moisture from the air, forming tellurite acid and causing deterioration. Simultaneously, the bisphenol A epoxy resin also acts as a coating medium, fully coating the tellurium oxide powder particles. The tellurium oxide powder is encapsulated within an organic film layer, eliminating the risk of exposure to toxic dust and isolating it from environmental moisture, preventing hydrolysis and deterioration of the powder surface. This provides a uniform reaction medium for the subsequent curing reaction, ensuring a uniform microstructure of the cured green body.
[0020] 3. The phenolic amine-modified amine curing agent designed in this invention complements the raw material tellurium oxide powder and bisphenol A epoxy resin. First, the phenolic hydroxyl groups of the phenolic compound are introduced into the amine molecule structure. These hydroxyl groups interact with the epoxy groups via hydrogen bonding, increasing the polarization and reactivity of the epoxy groups and accelerating the ring-opening addition reaction of the active hydrogen in the amine to the epoxy groups, thus achieving a catalytically accelerated curing effect. Second, the benzene ring structure of the phenolic compound is connected to the amine group through methylene bridges to form a rigid phenolic skeleton structure. This skeleton can increase the heat distortion temperature of the cured product, ensuring dimensional stability of the preform during subsequent heating and dewaxing. Finally, the modified curing agent molecule retains primary and secondary amine groups as the main active sites for crosslinking reactions with the epoxy groups.
[0021] 4. The tellurium oxide ceramic core green blocks prepared using the molding method of this invention exhibit excellent performance in terms of density, uniformity, and subsequent processability. The green block density in all embodiments described in the specification is consistently above 55%TD, meeting the density requirements for replacing the pressing molding process. Furthermore, the innovative molding method of this invention has significant advantages in terms of safety, environmental protection, and production adaptability. All operations are carried out under vacuum and sealed conditions, with no solid powder exposed to the operating environment throughout the process. This fundamentally avoids tellurium oxide powder spillage and aerosol formation, eliminating the risk of toxicity to operators and pollution to the surrounding environment, and meeting the stringent occupational safety and environmental protection requirements in the fields of nuclear energy and radioactive material preparation. Moreover, this molding method has a wide process window, allowing for flexible adjustment of process parameters to adapt to different batch sizes and production rhythms according to production needs. The cylindrical grooves in the metal container can be customized according to the target dimensions, achieving near-net-shape molding and reducing subsequent processing. This provides a reliable solution for the clean industrial production of tellurium oxide ceramic core blocks and has significant application value in the stable preparation of iodine-131 targets. Attached Figure Description
[0022] Figure 1 This is a schematic flowchart of the method for forming the tellurium oxide ceramic core block according to the present invention. Detailed Implementation
[0023] The present invention will be further described below with reference to preferred embodiments. The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values. These ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed herein. Unless otherwise specified, the experimental methods in the following embodiments are conventional methods, performed in accordance with the techniques or conditions described in the literature in this field or in accordance with the product instructions.
[0024] Unless otherwise specified, all materials and reagents used in the following examples are commercially available. Example 1 This embodiment provides a method for forming a tellurium oxide ceramic core, including the following steps: S1. Under vacuum and sealed conditions, tellurium oxide powder is dried and degassed. S2. Mix tellurium oxide powder and E-44 type bisphenol A epoxy resin at a mass ratio of 3:1 until uniform and stir to form slurry A; S3. Mix slurry A and phenolic amine modified amine curing agent at a volume ratio of 3:1 until homogeneous and stir to form slurry B; S4. Inject slurry B into the cylindrical grooved metal container, heat to 90℃, and maintain for 2 hours; S5. Heat the metal container to 600℃ to dewax, and keep it at that temperature for 2 hours to obtain the formed tellurium oxide ceramic core blank.
[0025] The green density of the tellurium oxide ceramic core was tested to be 55.3%TD (TD is the theoretical density).
[0026] Example 2 This embodiment provides a method for forming a tellurium oxide ceramic core, including the following steps: S1. Under vacuum and sealed conditions, tellurium oxide powder is dried and degassed. S2. Mix tellurium oxide powder and E-44 type bisphenol A epoxy resin at a mass ratio of 4:1 until uniform and stir to form slurry A; S3. Mix slurry A and phenolic amine modified amine curing agent at a volume ratio of 3:1 until homogeneous and stir to form slurry B; S4. Inject slurry B into a cylindrical grooved metal container and keep it at room temperature for 16 h. S5. Heat the metal container to 600℃ to dewax, and keep it at that temperature for 8 hours to obtain the formed tellurium oxide ceramic core blank.
[0027] The green density of the tellurium oxide ceramic core was tested to be 58.6%TD (TD is the theoretical density).
[0028] Example 3 This embodiment provides a molded tellurium oxide ceramic core block, the molding method of which includes the following steps: S1. Under vacuum and sealed conditions, tellurium oxide powder is dried and degassed. S2. Mix tellurium oxide powder and E-51 type bisphenol A epoxy resin at a mass ratio of 4:1 until uniform and stir to form slurry A; S3. Mix slurry A and phenolic amine modified amine curing agent at a volume ratio of 2:1 until homogeneous and stir to form slurry B; S4. Inject slurry B into the cylindrical grooved metal container, heat to 60℃, and maintain for 8 hours; S5. Heat the metal container to 600℃ to dewax, and keep it at that temperature for 4 hours to obtain the formed tellurium oxide ceramic core blank.
[0029] The green density of the tellurium oxide ceramic core was tested to be 57.1%TD (TD is the theoretical density).
[0030] Example 4 This embodiment provides a molded tellurium oxide ceramic core block, the molding method of which includes the following steps: S1. Under vacuum and sealed conditions, tellurium oxide powder is dried and degassed. S2. Mix tellurium oxide powder and E-51 type bisphenol A epoxy resin at a mass ratio of 3.5:1 until uniform and stir to form slurry A; S3. Mix slurry A and phenolic amine modified amine curing agent at a volume ratio of 2.5:1 until homogeneous and stir to form slurry B; S4. Inject slurry B into the cylindrical grooved metal container, heat to 80℃, and maintain for 10 h; S5. Heat the metal container to 650℃ to dewax, and keep it at that temperature for 6 hours to obtain the formed tellurium oxide ceramic core blank.
[0031] The green density of the tellurium oxide ceramic core was tested to be 57.8%TD (TD is the theoretical density).
[0032] The above description is merely an embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made based on the content of the present invention specification, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.
Claims
1. A method for forming a tellurium oxide ceramic core, characterized in that, Under vacuum conditions, dried and degassed tellurium oxide powder is mixed evenly with bisphenol A epoxy resin to form slurry A. Then, phenolic amine modified amine curing agent is added to slurry A and mixed evenly to form slurry B. Slurry B is poured into a metal container and left to stand. Then, it is heated and dewaxed. After heat preservation, a molded tellurium oxide ceramic core block is obtained. Phenolic amine modified amine curing agents are prepared by Mannich condensation reaction of phenolic compounds, aldehyde compounds and polyamine compounds. The amine value is 400-500 mgKOH / g and the viscosity is 300-1500 mPa·s.
2. The method for forming a tellurium oxide ceramic core block according to claim 1, characterized in that, The mass ratio of tellurium oxide powder to bisphenol A epoxy resin is (3-4):
1.
3. The method for forming a tellurium oxide ceramic core block according to claim 2, characterized in that, The bisphenol A epoxy resin is of type E-44 or type E-51.
4. A method for forming a tellurium oxide ceramic core block according to claim 1, characterized in that, The preparation steps of the phenolic amine modified amine curing agent are as follows: phenolic compounds, aldehyde compounds and polyamine compounds are added to a reaction vessel at a mass ratio of 300-500:500-800:100, and stirred and reacted at 80-120℃ for 2-4 h. After vacuum dehydration, the phenolic amine modified amine curing agent is obtained. The phenolic compound is any one or a combination of phenol, nonylphenol, cashew phenol, and m-cresol; the aldehyde compound is formaldehyde solution or paraformaldehyde; the polyamine compound is any one or a combination of diethylenetriamine, triethylenetetramine, and hexamethylenediamine.
5. The method for forming a tellurium oxide ceramic core block according to claim 1, characterized in that, The volume ratio of slurry A to phenolic amine modified amine curing agent is (2-3):
1.
6. A method for forming a tellurium oxide ceramic core block according to claim 1, characterized in that, Slurry B is poured into a metal container and left to stand for 2-16 hours.
7. A method for forming a tellurium oxide ceramic core block according to claim 6, characterized in that, Slurry B is injected into a metal container and heated to 60-90℃, then left to stand for 2-16 hours.
8. A method for forming a tellurium oxide ceramic core block according to claim 1, characterized in that, After the metal container containing slurry B is left to stand, it is heated to 550-700℃ for dewaxing, and the holding time is 2-8 hours.
9. A shaped tellurium oxide ceramic core block prepared by the method according to any one of claims 1 to 8.
10. A molded tellurium oxide ceramic core block according to claim 9, characterized in that, The relative density of the molded tellurium oxide ceramic core is greater than 55%.